Sozialperspektivität - theoretische Bezüge, Forschungsmethodik und wirtschaftliche Praktikabilität eines beziehungsdiagnostischen Konstrukts - Strack, Micha (Universitätsverlag Göttingen, 2004)
Social perspective defines the human skill of changing between the point of view of oneself and the other. It takes meta-perspectives and applies them to the different (suspected) point of views. If one knows how the interaction-partner sees the world, one can assume the partner´s willingness to act and consider it for one´s own plan of action.